Implementasi Etika Profesi dan K3L Pada Kegiatan Operasi dan Pemeliharaan Bendungan Jatibarang - Wulandari, Dyah Ari; Hadiyanto, H; Rizal Isnanto, R (Jurnal Profesi Insinyur Indonesia, 2023)
[Title: Implementation of Professional Ethics and HSE in Jatibarang Dam Operation and Maintenance Activities] Implementation of Dam Operation and Maintenance (OP) is very important to maintain dam safety and the sustainability of dam function. Operation and maintenance must be carried out in accordance with established procedures and a well-structured OP implementation program according to conditions of dam  and climate change. Dam Operation and Maintenance activities involve a lot of Engineering practice and need to pay attention to Health, and Environment (HSE). This study aims to determine the implementation of Professional Ethics and HSE in the operation and maintenance of the Jatibarang Dam. This research begins with conducting literature review and collecting secondary data. The collected data is then processed and the results are discussed and concluded. The operation and maintenance of the Jatibarang Dam includes operations, maintenance and monitoring activities, which must be planned and then held and reports its implementation. Dam operation is carried out by adjusting the water output of the reservoir. Dam maintenance is done to prevent damage or repair damage. While dam monitoring is carried out to find out symptoms of problems with the dam at an early stage. The implementation of professional ethics is manifested by managers in the form of responsibility, honesty, obedience, competence, teamwork and sustainable utilization. HSE has been implemented but managers have not fully implemented HSE Management System. HSE risk management which includes hazard identification, risk assessment and risk control has just been implemented for the dam safety. For The supporting work activities have not been carried out.